KEPENTINGAN AMERIKA SERIKAT DALAM MEMPERTAHANKAN PERDAGANGAN PRODUK APPLE INC DI KOREA SELATAN - Melda Asri; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explain about interest United State comerce product ofApple Inc at South Korean. Which South Korean have a product of smarthphonehas been to being the world. But, half of South Korean’s people more to useproduct of Apple Inc. At market, Apple Inc have more importent relation withUnited State. Other that relation, United State also have interest at South Koreanin econmic and politic. One of strategy United State to relaize the interest atSouth Korean are with defend comerce product of Apple Inc at South Korean.This research use kualitatif analisis, use the theory competitive adventage fromMichaele E. Potter. This research also use national interest concep and levelanalysis nation state. The writer used data which was collected from books,journal, thesis, and website to analysis the research. Finding, this research isdecicion of goverment United State by take outside right veto as to purpose for fillinterest economic and politic United State. Interest economic is get contributionto country and interest politik is attaiment purpose to get more power of alliancemilitary with South Korean.Key words: Interest, Apple Inc, Economic Politic, Superiority Competitive